Application of Supply Chain Management for Ensuring Productivity of Food Products - Nurtazina, Gulzhan; Byashev, Birzhan; Zhylkaidar, Arman; Bulegenova, Madina (International Journal of Supply Chain Management, 2020)
The globalization of the trade in animals and food has made food industry effiecency an international issue, which can be achieved through the employing the supply chain management system to trach the food in production, delivery and costumers. In modern conditions of production and sale of food raw materials and food products of animal origin, it is imperative to effectively supply chain manage the veterinary system to ensure health of animals and hence safety of food products consumed by the population. State regulation of the veterinary control in the supply chain system from the production sector is a major factor for monitoring food safety, therefore legislation of each state must provide for adequate policy on veterinary services and measures to be taken to respond to potential food safety hazard. This article studies the role of supply chain management system regulation in protecting the population from the unsafe food products.